Exploring women's experiences with persistent pain and pain management following breast cancer treatment: A qualitative study - Smith, Michelle D.; Manning, Joanne; Nielsen, Mandy; Hayes, Sandra C.; Plinsinga, Melanie L.; Coppieters, Michel W. (Frontiers in Pain Research, 2023)
This qualitative study aimed to explore experiences of women with persistent pain following breast cancer treatment, including their perceptions about the cause of their pain, how they manage their pain and their interactions with healthcare providers related to their pain during and following breast cancer treatment. Fourteen women who experienced pain for more than 3 months following breast cancer treatment were recruited from the general breast cancer survivorship community. Focus groups and in-depth, semi-structured interviews were conducted by one interviewer, audio-recorded, and transcribed verbatim. Transcripts were coded and analysed using Framework Analysis. Three main descriptive themes emerged from the interview transcripts: (1) characteristics of pain, (2) interactions with healthcare providers and (3) pain management. Women had various types and degrees of persistent pain, all of which they believed were related to breast cancer treatment. Most felt like they were not given enough information pre- or post-treatment and believed their experience and ability to cope with pain would have been better if they were given accurate information and advice about (the possibility of) experiencing persistent pain. Pain management strategies ranged from trial and error approaches, to pharmacotherapy, and to ‘just coping with the pain”. These findings highlight the importance of the provision of empathetic supportive care before, during and after cancer treatment that can facilitate access to relevant information, multidisciplinary care teams (including allied health professionals) and consumer support.